The Safety and Efficacy of Mini Percutaneous Nephrolithotomy During Learning Curve - Thapa, Bikash Bikram; Basnet, Bina; Rayamajhi, Bikash Bahadur; Thapa, Narayan; Bhandari, Bharat Bhadur (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: Since its introduction in 1976, percutaneous renal stone surgery has undergone several modifications. Reduction in size of access sheath was one of them which was first reported by Jackman in 1998. The miniaturisation of access sheath in Mini-Percutaneous Nephrolithotomy surgery has significantly reduced the intervention related morbidity with similar outcome as of standard Percutaneous Nephrolithotomy.Methods: This is a prospective cohort study where a single surgeon without previous experience of independent PCNL surgery performed Mini PCNL under controlled condition for renal stone sized 10 to 30 mm. The outcome was measured in terms of stone free rate and postoperative complications. The association of stone free rate and drop in haemoglobin level with different preoperative and operative variables were calculated with Pearson’s correlation test and p value